Pembelajaran 2 Raja-raja 5: Implikasi Kesembuhan Naaman dalam Konseling Krisis Kesembuhan Pada Masa Pandemi Covid-19 - Melpin Sihotang; Alvyn Cesarianto Hendriks; Stimson Hutagalung; Rolyana Ferinia (Davar : Jurnal Teologi, 2021)
The purpose of writing is to study 2 Kings 5 of Naaman's recovery as a motivation for crisis counseling during the Covid-19 Pandemi. The writing method is a descriptive analysis method, by reading, observing the entire contents of the text, seeing a description of the actions taken by the characters in the text, paying attention to the relationships that exist in the text and drawing the general meaning of the text. The meaning of the text is taken as a lesson in the implementation of crisis counseling. during a pandemi. The results of the study provide a lesson on how 2 Kings 5 stories of Naaman who experienced despair can be healed and the King of Israel who is depressed finds a solution. When Naaman and the King of Israel came to God through his prophet Elisha, Naaman was healed and even clean and the crisis of the king of Israel was resolved. During the Covid-19 Pandemi, there are many people who experience something similar to stress and even despair when they are positively affected by Covid-19. The Healing Study Naaman teaches that in any difficult situation, there is God who helps. The implication is that people affected by Covid-19 are motivated to get healing, when they come with faith in God.